Characterizing Interactions of Thioflavin-T with Native Proteins Especially Bovine Serum Albumin - Stratton, Caleb Matthew (East Carolina University, 2017)
Thioflavin T is a fluorescent probe used to monitor formation of cross [beta]-sheet rich amyloid fibrils. Involvement of the amyloid fibrils is implicated in more than 50 human diseases, such as Alzheimer's, Parkinson's and Prion's. The proteins responsible for each of these diseases many as well as model proteins have been used to unravel the process involved in native protein to amyloid transformation, especially, for drug design but with little success thus far. Bovine serum albumin (BSA), predominantly [alpha]-helical in constitution, is one such protein that has been observed to transform to [beta]-sheet rich amyloid. For our thesis project, we set on with these basic lines of evidence for ThT and BSA and devised a study outline. The study was divided into sub sections for better redressal compared to what was reported in literature viz., 1) Characterizing the steps involved in the transformation of BSA from native to amyloid state, 2) Develop methodology to gain information of as many steps as possible, 3) Identify the structural changes triggering BSA on pathway to fibrillation, 4) Computational comparison of the sites with chaperone binding sites and finally 5) if from point 4 we could observe chaperones interfering the aggregation process of BSA. During this thesis work, we observed an unexpected interaction of the reporter ThT molecule with the native BSA. We expanded this further and used a suite of standard proteins and found that ThT has the unlikely affinity to bind to some of the proteins, which are predominantly helical in nature. The present study thus details the aspects of interaction of ThT with BSA. Briefly, our Fluorescence data indicated a strong binding of ThT with BSA, ovalbumin and Alcohol Dehydrogenase. The binding was confirmed with ELISA type binding assays. Further, Circular dichroism showed ThT binding caused a minor structural disruption in the alpha helical content of the BSA which was supported by melting curves where BSA in the presence of ThT was 4 degrees less stable than in the absence of ThT. A control run of myoglobin exhibited no changes in the Tm studies with ThT. In addition, FTIR data exhibited marked changes in the BSA profiles in the presence and absence of ThT. Based on these data we ran the molecular docking simulation on ThT and BSA crystal structure and shortlisted two most predictable binding sites of ThT on BSA.
Keywords: Thioflavin-T; Fibrillation; Aggregation; Fluorescent probes; Amyloid; Proteins--Analysis